Pengembangan Sistem Manajemen Penjualan Toko Buku berbasis Website menggunakan Payment Gateway (Studi Kasus: Literasi Nusantara) - Ahmad Fathur Rahman; Achmad Arwan; Denny Sagita Rusdianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Management of book and sales are important for a bookstore. The problems that occur in the Literasi Nusantara bookstore are publishers who want to cooperate with the bookstores want them to have their own sales website and problems related to the bookstore's inventory management and sales that are still recorded manually. Publishers who want to cooperate with bookstores want to check about books sold by Literasi Nusantara through their own website. The process of managing book inventory and sales is still manual, causing the book and sales management processes to take a long time. Hopefully, this system can help the process of cooperation between the bookstore and publishers and help improve the efficiency of their sales management time. The waterfall software development model is used in the development process of this system. The stages performed in this research are literature study, requirements engineering, design, implementation, testing, and drawing conclusions and suggestions. This system uses website technology so that the bookstore system can be accessed by users via a web browser. The bookstore system has been tested using unit testing and integration testing (white box testing) as well as validation testing and compatibility testing (black box testing).